2015
DOI: 10.22514/sv102.122015.4
|View full text |Cite
|
Sign up to set email alerts
|

Immature granulocyte count on the new Sysmex XN-9000: performance and diagnosis of sepsis in the intensive care unit

Abstract: Introduction. The amount of immature leukocytes reflects marrow response to bacterial infection, and this may be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
3
1
Order By: Relevance
“…Karon et al [ 18 ] reported that the IG% and IG count were of limited utility in predicting sepsis in a study of patients admitted to the emergency department. Additionally, unlike the findings of our study, Buoro et al [ 19 ] reported that an IG < 10.0% was a valid cut-off for the diagnosis of sepsis in ICU patients. Ayres et al [ 20 ] reported that an IG% < 2.0% was adequate for excluding sepsis as a diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Karon et al [ 18 ] reported that the IG% and IG count were of limited utility in predicting sepsis in a study of patients admitted to the emergency department. Additionally, unlike the findings of our study, Buoro et al [ 19 ] reported that an IG < 10.0% was a valid cut-off for the diagnosis of sepsis in ICU patients. Ayres et al [ 20 ] reported that an IG% < 2.0% was adequate for excluding sepsis as a diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…In comparison studies, all routinely used CBC parameters were comparable and showed very high correlations between BC‐6000 and Sysmex XN with the same samples in terms of clinical usefulness by the Passing‐Bablok and Bland‐Altman analyses . And also, for the leukocyte differential parameters, BC‐6000 and manual microscopy have more consistent results, especially for monocytes and immature granulocytes when compared to the previous report . For the flagging ability studies of blasts, the sensitivity, specificity, and overall efficiency of BC‐6000 are 82.9%, 82.4%, and 82.6%, and it is an excellent performance for common clinical laboratory and better than Sysmex XE‐2100, which was reported to result in a very high rate of manual slide review in detecting blast, but a less specific and remarkable increase in the workload in the laboratory.…”
Section: Discussionmentioning
confidence: 56%
“…22 And also, for the leukocyte differential parameters, BC-6000 and manual microscopy have more consistent results, especially for monocytes and immature granulocytes when compared to the previous report. 8,23,29 For the flagging ability studies of blasts, the sensitivity, specificity, and overall efficiency of BC-6000 are 82.9%, 82.4%, and 82.6%, and it is an excellent performance for common clinical laboratory and better than Sysmex XE-2100, 30 which was reported to result in a very high rate of manual slide review in detecting blast, but a less specific and remarkable increase in the workload in the laboratory. This phenomenon is inconsistent with the flagging performance of Sysmex XN (97%) which was reported by Seo.…”
Section: Throughput Studymentioning
confidence: 99%
“…Nonetheless, neutrophils in the form of left shift remain an important part of sepsis pathobiology and the body's response to infection, and are considered one of the earliest indicators of sepsis. Studies done by Buoro et al, 12 Bourne et al, 13 MacQueen et al 14 , and others have validated immature granulocyte count by Sysmex as an indicator of the left shift and thus sepsis.…”
Section: Discussionmentioning
confidence: 98%